2023
DOI: 10.1093/lambio/ovad053
|View full text |Cite
|
Sign up to set email alerts
|

Development of an animal-free nitrogen source for the liquid surface culture of Cordyceps militaris

Abstract: Cordyceps militaris is a medicinal mushroom in Asia in the twenty-first century, which cordycepin is a significant bioactive compound. This study investigated the effect of culture conditions and vegetable seed extract powder (VSEP) as a supplementary source of animal-free nitrogen on the production of cordycepin by C. militaris in liquid surface culture. The highest cordycepin production was observed under SBEP conditions, and 80 g/L of SBEP supplementation increased cordycepin production to 2.52 g/L, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The addition of 80 g/L soybean extract powder (SBEP) increased the cordycepin production up to 2.52 g/L, which was greater than the control (peptone). Quantitative polymerase chain reaction (qPCR) result revealed that 80 g/L SBEP significantly increased the expression of genes linked with the carbon metabolic pathway, amino acid metabolism, and two crucial genes involved in the cordycepin biosynthesis ( Cns1 and NT5E ) compared to peptone-supplemented culture ( Sripilai et al, 2023 ).…”
Section: Strain Fermentationmentioning
confidence: 99%
“…The addition of 80 g/L soybean extract powder (SBEP) increased the cordycepin production up to 2.52 g/L, which was greater than the control (peptone). Quantitative polymerase chain reaction (qPCR) result revealed that 80 g/L SBEP significantly increased the expression of genes linked with the carbon metabolic pathway, amino acid metabolism, and two crucial genes involved in the cordycepin biosynthesis ( Cns1 and NT5E ) compared to peptone-supplemented culture ( Sripilai et al, 2023 ).…”
Section: Strain Fermentationmentioning
confidence: 99%